OMICRON SARS-CoV-2 VARIANT, B.1.1.529: SEVERITY, TRANSMISSION, MUTATION, AND EFFICACY OF CURRENT VACCINES - SAADH, MOHAMED J. (International Journal of Applied Pharmaceutics, 2022)
The Omicron variant (B.1.1.529) is a variant of SARS-CoV-2 with more than 50 mutations; this led to increase transmissibility or lead to immune escape. Therefore, WHO predicts it to be more dangerous than the previous variant, although it is not as severe as the previous variant. This review aims to provide an overview of SARS-CoV-2 symptoms, severity, mutations, and the effectiveness of treatments and vaccines against this novel coronavirus, as well as the effectiveness of current diagnostic tests.